Ruthenium Picolinate Complex as a Redox Photosensitizer With Wide-Band Absorption - Tamaki, Yusuke; Tokuda, Kazuma; Yamazaki, Yasuomi; Saito, Daiki; Ueda, Yutaro; Ishitani, Osamu (Frontiers in Chemistry, 2019)
Ruthenium(II) picolinate complex, [Ru(dmb)2(pic)]+ (Ru(pic); dmb = 4,4’-dimethyl-2,2’-bipyridine; Hpic = picolinic acid) was newly synthesized as a potential redox photosensitizer with a wider wavelength range of visible-light absorption compared with [Ru(N^N)3]2+ (N^N = diamine ligand), which is the most widely used redox photosensitizer. Based on our investigation of its photophysical and electrochemical properties, Ru(pic) was found to display certain advantageous characteristics of wide-band absorption of visible light (abs < 670 nm) and stronger reduction ability in a one-electron reduced state (E1/2red = –1.86 V vs. Ag/AgNO3), which should function favorably in photon-absorption and electron transfer to the catalyst, respectively. Performing photocatalysis using Ru(pic) as a redox photosensitizer combined with an Re(I) catalyst reduced CO2 to CO under red-light irradiation (ex > 600 nm). TONCO reached 235 and CO was 8.0%. Under these conditions, [Ru(dmb)3]2+ (Ru(dmb)) is not capable of working as a redox photosensitizer because it does not absorb light at  > 560 nm. Even in irradiation conditions where both Ru(pic) and Ru(dmb) absorb light (ex > 500 nm), using Ru(pic) demonstrated faster CO formation (TOFCO = 6.7 min–1) and larger TONCO (2347) than Ru(dmb) (TOFCO = 3.6 min–1; TONCO = 2100). These results indicate that Ru(pic) is a superior redox photosensitizer over a wider wavelength range of visible-light absorption.